Implementasi Program Bimwin Catin untuk Mewujudkan Keluarga Berkualitas di Kecamatan Sukolilo Kota Surabaya - Saskia Nisa Setiaatmitha; Ghulam Maulana Ilman (Universitas 17 Agustus 1945 Semarang, Indonesia, 2023)
By looking at the problems of family life that occur, Surabaya City still lacks quality families. The Decree of the Director General of Islamic Guidance of the Ministry of Religious Affairs Number 379 of 2018 concerning Implementation Guidelines for Marriage Guidance for Prospective Brides was made to overcome existing problems. This study aims to determine the implementation of the Bimwin Catin program to create quality families in Sukolilo District. The research uses a qualitative approach method. The results showed that the implementation of Bimwin Catin has been carried out well in the KUA of Sukolilo Subdistrict as an effort to realize Quality Families by involving three agencies, namely DP3APPKB, the Health Office, and the Ministry of Religion. The implementation of Bimwin Catin in Sukolilo Sub-district still has obstacles regarding the budget and the lack of interest of catin couples to participate in programs like this because they feel they do not need and are not important. Funding providers should be able to provide funds in accordance with the needs of program implementation and make it mandatory for prospective brides to participate in Bimwin Catin so that they are ready for family life.